Atopic Dermatitis and its Severity Correlation With Absolute Eosinophil Counts - Pandey, Sumit; Jha, Smita; Pokharel, Nitesh Raj; Kadel, A. (Journal of Nepalgunj Medical College, 2018)
Background: Atopic dermatitis is one of the common skin disease affecting children and adults. Atopic dermatitis is a common and difficult to manage allergic condition. Till date severity of atopic dermatitis is graded only by clinical findings, which has greater means of individual variation, so a laboratory value may uniform the grading and eosinophils are always thought to be associated with allergic conditions.Objectives: To assess the severity of atopic dermatitis by peripheral blood eosinophil count and SCORAD index, and also to explore  relationship between personal history of atopy, family history of atopy, severity of disease and absolute eosinophil count.Material and Method: This study is a hospital based Cross sectional descriptive study conducted in the Department of Dermatology, Venereology and Leprology of Nepalgunj Medical College Teaching Hospital, Kohalpur between March 2017 to February 2018. Total  of 53 patients fulfilling the criteria of UK refinement of Hanifin and Rajka's criteria for atopic dermatitis presented to the OPD of  dermatology department at Kohalpur were included in the study.Result: A total of 53 patients were enrolled, mean age of the patients was 6.08 (SD 2.83) years and mean age of onset of disease was2.95 (SD 1.57) years. Mean AEC was 537.17(SD 343.92)/mm3 and higher mean AEC was significantly (P